A quantitative method to analyse F-actin distribution in cells - Zonderland, Jip (MethodsX, 2019)
Changes in actin structure and distribution are involved in many cellular processes, such as differentiation, proliferation and migration. Differences in cell shape and size make the analysis of actin distribution difficult. Here, we have developed a Fiji macro that analyzes the distribution of actin within the cell, regardless of cell size or shape. The staining intensity is measured along an automatically drawn line over the cell. The intensity data is divided in equal bins, making the analysis insensitive to changes in cell size or shape. We have also created an R script that further processes the acquired data. Together, final data can be acquired within minutes from a set of images, with freely available software. We demonstrate our method with F-actin staining of cytochalasin D treated cells. The advantages of our methods are: • The analysis is not influenced by cell shape or size; • All steps in the analysis are shown, and can therefore easily be verified for each image; • All software required for the analysis is freely available.